Student academic freedom policy in Egyptian Higher Education; case study: Faculty of Economics and Political Science, Cairo University. - Esmat, Israa Medhat Tawfik (AUC Knowledge Fountain, 2016)
The study aimed to explore stakeholders’ perceptions of an effective policy for student academic freedom in Egyptian Higher Education. The significance of the study stemmed from both theoretical and practical considerations. Theoretical considerations originated from the dearth of studies tackling student academic freedom, while practical considerations, as reported by local and international non-governmental organizations, were related to infringements on student academic freedom in Egyptian Higher Education. The study’s main research question was: How do students and faculty members perceive elements of an effective policy for student academic freedom in Egyptian Higher Education? In this context, the study explored the perceptions of students and faculty members regarding the parameters of student academic freedom along with the elements of an effective policy to protect such freedom. The case study selected for this study was the Faculty of Economics and Political Science (FEPS), Cairo University. A qualitative methodology was adopted, where 25 in-depth and semi-structured interviews were conducted with a purposive sample of students and faculty members. The collected data demonstrated that participants conceptualized student academic freedom in terms of three elements: freedom to conduct research, freedom of expression inside classroom, and freedom to select specialization and courses. In addition, participants referred to a number of internal and external sources of threat to student academic freedom in FEPS. Internal sources of threat included pedagogical methods, political indoctrination, and professors’ authority. External sources of threat comprised lack of university autonomy, climate of fear, restrictions on data collection, and imposed red-lines. To eliminate sources of threat, participants put forth a number of suggested policies and solutions which included: providing a legal protection for faculty and student academic freedom, embedding academic freedom in FEPS internal regulations, and raising awareness on academic freedom issues. Based on previous literature, international experiences, and interview data, the study suggested a number of recommendations regarding an effective policy for student academic freedom in Egyptian Higher Education. Recommendations included multiple policy levels and actors and covered Higher Education policies, FEPS internal policies and regulations, civil and political rights and freedoms, and raising awareness and advocacy.